2020
DOI: 10.3390/ijms21239021
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Endoglin as a Potential Biomarker of Nonalcoholic Steatohepatitis (NASH) Development, Participating in Aggravation of NASH-Related Changes in Mouse Liver

Abstract: Nonalcoholic steatohepatitis (NASH) is characterized by hepatic steatosis with inflammation and fibrosis. Membrane endoglin (Eng) expression is shown to participate in fibrosis, and plasma concentrations of soluble endoglin (sEng) are increased in patients with hypercholesterolemia and type 2 diabetes mellitus. We hypothesize that NASH increases both hepatic Eng expression and sEng in blood and that high levels of sEng modulate cholesterol and bile acid (BA) metabolism and affect NASH progression. Three-month-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…To induce NASH, C57BL/6 male mice were fed an F diet over 24 weeks. In comparison with a chow diet, the F diet induced significant elevations in body weight; liver weight; liver to body weight ratio (%); serum alanine aminotransferase (ALT), an indicator of hepatocellular injury; alkaline phosphatase (ALP), a marker of cholestatic liver impairment; triglycerides (TG); and soluble endoglin ( Figure 1 )—a recently suggested marker of liver fibrosis in NASH [ 28 ]. Atorvastatin effectively reduced plasma ALT and TG concentrations ( Figure 1 ), indicating its positive effect on liver injury.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To induce NASH, C57BL/6 male mice were fed an F diet over 24 weeks. In comparison with a chow diet, the F diet induced significant elevations in body weight; liver weight; liver to body weight ratio (%); serum alanine aminotransferase (ALT), an indicator of hepatocellular injury; alkaline phosphatase (ALP), a marker of cholestatic liver impairment; triglycerides (TG); and soluble endoglin ( Figure 1 )—a recently suggested marker of liver fibrosis in NASH [ 28 ]. Atorvastatin effectively reduced plasma ALT and TG concentrations ( Figure 1 ), indicating its positive effect on liver injury.…”
Section: Resultsmentioning
confidence: 99%
“…Reverse-transcription polymerase chain reaction (qRT-PCR) was conducted via the Quantstudio 7 HT fast RT-PCR system (Applied Biosystems, Foster City, CA, USA) as described previously [ 28 ]. The primers used for analysis are specified in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soluble endoglin represents an interesting biomarker of vascular pathology in both clinical and experimental studies [23]. More interestingly, several studies demonstrated potential harmful effects of sEng in endothelial function [12], liver metabolism [24], and development of NASH [25], suggesting that high levels of sEng might be considered as a risk factor of development of vascular alteration. Indeed, placenta-derived sEng from pregnant preeclamptic women is able to increase vascular permeability and induce arterial hyper-tension in vivo, suggesting that sEng plays an essential role in the pathogenesis of arterial hypertension, proteinuria, and glomerular endotheliosis [26].…”
Section: Discussionmentioning
confidence: 99%
“…sEng is the cleavage product of the extracellular domain of Eng upon the enzymatic activity of matrix metalloproteinases (MMP-14 and MMP-12) ( 12 , 13 ). It is released into the circulation in various pathological conditions, such as arterial hypertension, type II diabetes mellitus ( 14 ), non-alcoholic steatohepatitis ( 15 ), familial hypercholesterolemia ( 16 , 17 ), and preeclampsia ( 18 ); and also in patients with atherosclerosis who had increased levels of total cholesterol, LDL, triglycerides and decreased levels of HDL ( 19 ). Moreover, increased levels of sEng correlate with complications of diabetes, such as retinopathy, peripheral neuropathy, or nephropathy ( 20 – 23 ).…”
Section: Introductionmentioning
confidence: 99%